2021
DOI: 10.1101/2021.10.28.466227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observation of non-dormant persister cells reveals diverse modes of survival in antibiotic persistence

Abstract: Bacterial persistence is a phenomenon in which a small fraction of isogenic bacterial cells survives a lethal dose of antibiotics. It is generally assumed that persistence is caused by growth-arrested dormant cells generated prior to drug exposure. However, evidence from direct observation is scarce due to extremely low frequencies of persisters, and is limited to high persistence mutants or to conditions that significantly increase persister frequencies. Here, utilizing a microfluidic device with a membrane-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 50 publications
(108 reference statements)
7
16
1
Order By: Relevance
“…In contrast to previously described characteristics of persiter cells, after release from antibiotics, we did not observe resumption of normal growth within 2-4 hours (3,4). Our findings hence support studies that explored persisters derived from exponentially growing cells that showed longer lag times to regain growth, note these cells had been growth arrest during drug exposure, or highlighting substantial variation in lag times after antibiotic exposure release (10,25,47). A lack of growth resumption, as we found, is also a characteristic of persister type II cells and VBNC cells, however VBNC are found in complete growth arrest and are characterized by a small cell size, and persister type II cells are not environmentally induced but predetermined (18,26), features not found in our study and other studies (10).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In contrast to previously described characteristics of persiter cells, after release from antibiotics, we did not observe resumption of normal growth within 2-4 hours (3,4). Our findings hence support studies that explored persisters derived from exponentially growing cells that showed longer lag times to regain growth, note these cells had been growth arrest during drug exposure, or highlighting substantial variation in lag times after antibiotic exposure release (10,25,47). A lack of growth resumption, as we found, is also a characteristic of persister type II cells and VBNC cells, however VBNC are found in complete growth arrest and are characterized by a small cell size, and persister type II cells are not environmentally induced but predetermined (18,26), features not found in our study and other studies (10).…”
Section: Discussionsupporting
confidence: 83%
“…Our findings suggest additional diversity of modes of phenotypic resistance, given that we show previously undescribed combination of characteristics. Compared to previous persister studies that quantify fractions of <0.1% persisters (24,8,10,25), we reveal a substantial larger fraction (~25%) of cells that survived 1.5 hours of antibiotic exposure, independent of the level of antibiotics (Fig. 1a, see also findings at cell culture for <64 μg/ml; Fig.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations